Feasibility study of replacing part of cement by igneous rock powder as cementitious material: based on mortar macroscopic properties and microstructure - Zhi Li; Zhenhua Zhao; Fushan Ma; Wenjin Di; Wenjin Di; Xuanhao Cao; Zhenqing He; Bowen Guan (Frontiers in Materials, 2024)
To address the increasing demand for cement and promote sustainable development, the utilization of igneous rock powder as a supplementary material to partially replace cement has emerged as an effective strategy. In this study, the fluidity and mechanical properties of the igneous rock powder-cement (IRP-OPC) composite system were investigated, and the hydration product and microstructure of IRP-OPC were analyzed by using TG/DSC, N2 adsorption-desorption curve (BET) and SEM. The experimental findings demonstrate that the performance of the andesite powder-cement composite cementing system (AP-OPC) surpasses that of tuff powder-cement slurry (TP-OPC) and granite powder-cement slurry (GP-OPC). When the dosage of andesite powder (AP) is 5%–15%, the flowability, flexural strength and compressive strength of cement mortar are improved. When the dosage is 10%, the 28-day compressive strength is 48.3 MPa. Under the condition of low content (10%), part of Ca(OH)2 is fully consumed by active SiO2 in AP and reacts to form C-S-H. Hydration products and AP particles with small particle size are filled into the structural gap, which refines the pore structure of cement slurry, and the increase in compactness provides support for the development of strength in the later stage. The use of 5%–15% AP instead of OPC can improve fluidity and meet the strength requirements of P.O 42.5 Portland cement. This substitution not only reduces engineering costs but also enhances resource utilization.